5-Methylcytosine (m5C) modification in peripheral blood immune cells is a novel non-invasive biomarker for colorectal cancer diagnosis - Yin, Haofan; Huang, Zhijian; Niu, Shiqiong; Ming, Liang; Jiang, Hongbo; Gu, Liang; Huang, Weibin; Xie, Jinye; He, Yulong; Zhang, Changhua (Frontiers in Immunology, 2022)
Current non-invasive tumor biomarkers failed to accurately identify patients with colorectal cancer (CRC), delaying CRC diagnosis and thus leading to poor prognosis. Dysregulation of 5-Methylcytosine (m5C) RNA has gradually been reported in various cancers, but their role in tumor diagnosis is rarely mentioned. Our study aimed to determine the role of m5C methylation modification in blood immune cells for the diagnosis of CRC. Peripheral blood samples were obtained from a total of 83 healthy controls and 196 CRC patients. We observed that m5C RNA contents in blood immune cells of CRC patients were markedly enhanced in both training set and validation set. Moreover, levels of m5C increased with CRC progression and metastasis but reduced after treatment. Compared with common blood tumor biomarkers, m5C levels in peripheral blood immune cells had superior discrimination and reclassification performance in diagnosing CRC. Besides, bioinformatics and qRT-PCR analysis identified increased expression of m5C-modified regulators NSUN5 and YBX1 in CRC patients’ blood. A series of animal models and cell co-culture models further demonstrated that CRC tumor cells could increase immune cells’ m5C levels and m5C-modified regulators. Monocyte was the predominant m5C-modified immune cell type in CRC patients’ blood by Gene set variation analysis (GSVA). Taken together, m5C methylation modification in peripheral blood immune cells was a promising biomarker for non-invasive diagnosis of CRC.